Incidencia de la depresión en el ámbito familiar de un adulto de 30 años de edad de la ciudad de Babahoyo - Iza Herrera, Alison Soleil (2023)
The topic to be developed in this case study is “Incidence of depression in the family environment of a 30-year-old adult from the city of Babahoyo” with the objective of identifying the incidence of the topic raised in the lines of research of the degree. “Clinical and forensic” and the subline “Individual and/or group psychotherapies”. Although it is true that depression is a disorder that affects not only the person who suffers from it directly, but also the circle where it develops, as in this case it is the family context, these being our variables to study "Depression" and "Family". The patient's predisposing factor was 3 months ago due to the loss of his source of income, which was a family business which with great effort he obtained and had been working for years, which had to close due to constant threats and extortion. Not working has caused negative automatic thoughts in the patient; these cognitive distortions generate behavioral effects.The research is descriptive because the researcher aims to describe and measure the range independently of the study variables with a mixed approach since qualitative and quantitative assessments were obtained, for which techniques such as observation, semi-structured interview, clinical history and psychometric tests. A psychotherapeutic panel was carried out, thus achieving the presumptive diagnosis. Finally, the therapeutic approach that was established was that of the cognitive behavioral technique (CBT), which managed to significantly reduce the patient's symptoms.